Responses of bats to forest fragmentation at Pozuzo, Peru - Mena, José Luis (2010)
Forest fragmentation and deforestation are among the major threats to Peruvian bats conservation. Unfortunately,information about the effects of these threats above 500 m elevation is lacking. In this study, I assessedbat responses to fragmentation in Pozuzo (Pasco) at a landscape scale approach. I evaluate two hypothesesregarding the role of bats as indicators of habitat disturbance. The first prediction says that landscapes highlydisturbed will show higher abundances of habitat generalist species such as frugivorous bats belonging to thesubfamilies Stenodermatinae and Carollinae. The second prediction regards that landscapes with greater forestcover will show higher abundance of habitat specialist species such as animalivorous bat species belongingto the subfamily Phyllostominae, a guild sensitive to forest disturbance. I found evidence supporting the animalivoroushypothesis but it was partial to the frugivorous hypothesis. This study highlights the importance offorest fragments to bat conservation in human-modified landscapes.